Superfast Full-Scale GPU-Accelerated Global Routing - Lin, Shiju; Wong, Martin D.F. (2022 IEEE/ACM International Conference On Computer Aided Design (ICCAD), 2022)
Global routing is an essential step in physical design. Recently there are works on accelerating global routers using GPU. However, they only focus on certain stages of global routing, and have limited overall speedup. In this paper, we present a superfast full-scale GPU-accelerated global router and introduce useful parallelization techniques for routing. Experiments show that our 3D router achieves both good quality and short runtime compared to other state-of-the-art academic global routers.